Monopsony Power and Poverty: The Consequences of Walmart Supercenter Openings - Lukas Lehner; Zachary Parolin; Clemente Pignatti; Rafael Pintro Schmitt (Institute of Labor Economics (IZA), 2024)
Prior research suggests that Walmart Supercenters exert substantial power over the low-wage labor market, though the consequences of Supercenter openings on household incomes and public finances are less clear. This study uses restricted-access Panel Study of Income Dynamics data from 1970 to 2019 to study how Walmart Supercenter openings affect poverty, tax liabilities, and receipt of income transfers. Using a stacked difference-in-differences approach, we find that the opening of a Supercenter leads to a 2 percentage point (16%) increase in poverty. This increase is channeled through declining annual earnings and persists for 10 years following the Supercenter's entry. Increases in poverty are particularly strong for younger and less-educated adults, and for adults with pre-treatment incomes below the national median. Moreover, Walmart Supercenter openings lead to a 200 (or 16%) per household per year increase in government income transfers received, and a 920 (or 5%) per household per year decrease in tax revenues.
Keywords: 32; J23; J31; J42; R23; 330; poverty; monopsony power; Walmart; local labor markets; economic inequality